Ergodic theory, open dynamics, and coherent structures - Bose, Christopher; Froyland, Gary; Bahsoun, Wael (Springer Proceedings in Mathematics & Statistics, 2014)
This book is comprised of selected research articles developed from a workshop on Ergodic Theory, Probabilistic Methods and Applications, held in April 2012 at the Banff International Research Station. It contains contributions from world leading experts in ergodic theory, dynamical systems, numerical analysis, fluid dynamics, and networks. The volume will serve as a valuable reference for mathematicians, physicists, engineers, physical oceanographers, atmospheric scientists, biologists, and climate scientists, who currently use, or wish to learn how to use, probabilistic techniques to cope with dynamical models that display open, coherent, or non-equilibrium behavior.